COLLABORATIVE GOVERNANCE DALAM PELAKSANAAN MUSAYAWARAH PERENCANAAN PEMBANGUNAN (MUSRENBANG) DI KOTA BANDUNG - Hajiji, Merdi; Rudiansah, Bambang (Universitas Bina Taruna Gorontalo, 2025)
This research aims to find out how development planning deliberation in Bandung City is a crucial aspect in local government planning, but the development carried out so far tends to be centralised and dominated by the local government with little contribution from the community. So in this case, collaborative governance in development planning deliberations is believed to be able to improve the quality of development planning oriented towards regional progress and community welfare. This research aims to examine collaborative governance in the implementation of development planning deliberations and the factors that influence collaborative governance in development planning in Bandung City, such as face-to-face dialogue, building trust, commitment to the process, shared understanding and short-term results, this is needed to determine the extent of community participation related to local government work programs which ultimately provides a statement that development planning deliberations in Bandung City are not optimal so that other approaches besides collaborative governance are needed for community participation. In addition, this research uses a descriptive qualitative research design where research data is obtained through observation, interviews and documentation.